FOTODEGRADASI ZAT WARNA METHYLENE BLUE DENGAN SINAR UV DAN FOTOKATALIS NANOPARTIKEL PERAK - Suprihatin, I. E.; Suat, R. M.; Negara, I. M. S. (Jurnal Kimia (Journal of Chemistry); Vol. 16, No.2, Juli 2022, 2022)
The textile industry is one of the producers of liquid waste that contains many synthetic dyes and difficult to decompose such as methylene blue (MB). Approximately 15-20% of the MB products that cannot be reused will go into the wastewater which eventually be drained into the catchment waters. This causes a variety of negative impacts, especially in the water environment. One way to prevent this problem is by decomposing the dye using UV light and accelerating the decomposition process with the photocatalysts, namely silver nanoparticles. The purpose of this study is to determine the optimal conditions for the photodegradation process of MB dyes, and the effectiveness of the degradation of MB dye under optimal conditions. The search was conducted by firstly finding the optimal conditions of the photocatalyst / NPAg volume, irradiation time, and pH. The optimal condition was then applied to photodegrade various concentrations of MB to determine the effectiveness of the process. The results showed the optimal condition of MB photodegradation was 10 mL of photocatalyst / NPAg, 60 minute irradiation time at pH 4. Under such condition, the method effectively degraded 98.21% of100 ppm MB. The method used is also effective for MB up to 150 ppm because it is able to degrade almost 100%. Keywords : photocatalyst, photodegradation, NPAg, methylene blue, plumeria rubra.